Diversity management strategy for military skills development system recruits : a cross-cultural approach for the South African National Defence Force, Air Force Base Gymnasium, Limpopo Province - Mamabolo, Mamogobo Rosinah (My University, 2025)
The post-apartheid era in South Africa created an environment where people of different socio-economic and racial orientations can work together on an equal basis. Thus, citizens come to the work environment with diverse socio-cultural values, which influence their perceptions of communication within any given organisational context. The South African National Defence Force (SANDF) training environment comprises diverse socio-cultural aspects including race, language, class and gender, where recruits are trained in one environment despite their socio-cultural differences. This calls for effective intercultural and cross-cultural communication during Basic Military Training (BMT) within the SANDF. This study explored the impact of diversity on BMT among recruits in the SA Air Force Gymnasium, Hoedspruit in the Limpopo province and aimed to develop a cross-cultural communication strategy for diverse Military Skills Development System (MSDS) recruits undertaking BMT training at the SA Air Force Gymnasium. To understand the nature of diversity and its effect on workgroup communication and progress, the study employed Oetzel’s (2005) Effective Intercultural Workgroup Theory, Kim’s (1988) Cross-cultural Adaptation Theory and Burgoon, Stern and Dillman’s (1995) Interaction Adaptation Theory. A qualitative research method was employed for this study. Purposive sampling was used to select the SA Air Force Gymnasium due to the diversity characteristics of its recruits. Quota sampling was used to acquire BMT recruits, instructors and squadron managers based on their language, race and gender aspects desirable for the study. Data were collected through three focus group discussions which consisted of 30 MSDS (BMT) recruits, semi-structured interviews with five instructors and two squadron managers as well as participant-observation. A reflexive thematic analysis was used to generate discursive themes and analyse the findings of the study. Additionally, Microsoft (MS) Excel was used to manage the numerical (demographic) data of participants. This study revealed that BMT emerges with diverse recruits from different gender, racial, cultural, linguistic, religious affiliation and African spirituality backgrounds which are carried out to cross-cultural interactions and therefore result in cross-cultural communication tensions, misunderstandings, misperceptions and misconceptions amongst the diverse communicators. Diversity manifestation elements (gender, culture, race, language and religious and African spirituality beliefs) are perceived assignificant factors which result in cross-cultural communication barriers. Amongst others, the study revealed that there is an interdependent relationship between cognition, lived experiences, culture and communication. Culture is automatically brought to the cross-cultural communication process of diverse recruits leading to ineffective cross-cultural communication. Additionally, the level of cross-cultural communication knowledge and lived experiences of military personnel determine the failure or the success of cross-cultural communication. Various cross-cultural communication strategies which include diversity educational programmes, acculturation, interpretation, regulatory frameworks and campaigns are perceived as effective strategies and approaches to effective cross-cultural interactions during BMT.
Thesis (Ph. D. (Communication Studies)) -- University of Limpopo, 2025
Keywords: Cross-Cultural Communication; Culture; Diversity; Cross-cultural communication; Cross-cultural orientation; Language and languages -- Variation; Cultural pluralism; Language and culture -- History; Cross-cultural orientation -- South Africa -- Limpopo; Communication